2019
DOI: 10.37107/jhas.23
|View full text |Cite
|
Sign up to set email alerts
|

Application of Social Cognitive Theory in Obesity Prevention: A Rapid Review

Abstract: Obesity, as a result of including the chronic positive energy balance, is associated with many chronic diseases. Prevalence of obesity is increasing worldwide, including in selected developing countries, from previous very low status. Association or causality of one or more constructs of social cognitive theory to prevent and control obesity is paramount for program interventions. We searched titles and abstracts using End Note Software and then approached original articles in databases of PubMed, Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Reported theory use was low, but strategies targeting SCT constructs were commonly used in many interventions. Prior research (72,73) has shown the use of one or more SCT constructs in healthy eating interventions is mostly effective (72,73) . Moreover, a review on the effectiveness of two or more healthy behavioural approaches saw a small but significant benefit when controlling both diet and physical activity compared with one behavioural approach (74) .…”
Section: Discussionmentioning
confidence: 99%
“…Reported theory use was low, but strategies targeting SCT constructs were commonly used in many interventions. Prior research (72,73) has shown the use of one or more SCT constructs in healthy eating interventions is mostly effective (72,73) . Moreover, a review on the effectiveness of two or more healthy behavioural approaches saw a small but significant benefit when controlling both diet and physical activity compared with one behavioural approach (74) .…”
Section: Discussionmentioning
confidence: 99%
“…These results support the effectiveness of applying the SCT to design healthy lifestyle behavior promotion and obesity prevention programs. To address the limited effects that SCT-based obesity prevention programs have had on preventing and treating obesity in adolescents, SCT constructs may need to be integrated with ecological components to achieve greater effects (Chiranjivi et al, 2018). Aligned with this contention, the Happy Family, Healthy Kids program incorporated the ecological perspective of intrapersonal (preschoolers), interpersonal (parents), and environmental (day care, home) influence into the program to increase the effects.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, increased friend support correlated with greater %EWL. This is consistent with previous work showing that theory is critical to help investigators explain intervention effects on weight loss and PA. 44,45 A HC intervention, such as the one implemented in this study, attempts to enhance aspects of behavior related to the social and the cognitive domain. The findings of Jimison et al 46 indicate that HC improves social interactions and ratings of social satisfaction while decreasing loneliness.…”
Section: 5%mentioning
confidence: 99%